Human ACE2 Polymorphisms from Different Human Populations Modulate SARS-CoV-2 Infection - Pan Hu; Vanessa L. Bauer; Sara L. Sawyer; Felipe Diaz-Griffero (Viruses, 2022)
The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in over 6 million deaths worldwide. The high variability in COVID-19 symptoms remains one of the most interesting mysteries of the pandemic. Genetic and environmental factors are likely to be key determinants of COVID-19 symptomatology. Here, we explored ACE2 as a genetic determinant for SARS-CoV-2 infection and COVID-19 symptomatology. Each human genome encodes two alleles of ACE2, which encodes the cell entry receptor for SARS-CoV-2. Here, we determined whether naturally occurring human ACE2 (hACE2) polymorphisms in the human population affect SARS-CoV-2 infection and the severity of COVID-19 symptoms. ACE2 variants S19P, I21V, E23K, K26R, K31R, N33I, H34R, E35K, and T92I showed increased virus infection compared to wild-type ACE2; thus, these variants could increase the risk for COVID-19. In contrast, variants D38V, Y83H, I468V, and N638S showed reduced infection, indicating a potential protective effect. hACE2 variants K26R and T92I increased infection by three-fold without changing the levels of ACE2 on the surface of the cells, suggesting that these variants may increase the risk of severe COVID-19. On the contrary, hACE2 variants D38V and Y83H decreased SARS-CoV-2 infection by four- and ten-fold, respectively, without changing surface expression, suggesting that these variants may protect against severe COVID-19. Remarkably, all protective hACE2 Polymorphisms were found almost exclusively in Asian populations, which may provide a partial explanation for the low COVID-19 mortality rates in Asian countries. Thus, hACE2 polymorphisms may modulate susceptibility to SARS-CoV-2 in the host and partially account for the differences in severity of COVID-19 among different ethnic groups.